Socio-scientific Issue around the Mahakam River: A STEM Activity Supported with Animated Video Development - Sari, Erna; Wandira, Ayu Ramadani; Sholeh, Muhammad; Syam, Muliati; Sulaeman, Nurul Fitriyah; Nuryadin, Atin (Universitas Muhammadiyah Mataram, 2026)
This research aims to develop a STEM–Engineering Design Process (STEM–EDP) student worksheet integrated with animated learning videos contextualized through socio-scientific issues (SSI) related to the Mahakam River ecosystem. The development was motivated by the lack of learning materials in junior high school science that meaningfully connect scientific concepts with local environmental problems while promoting higher order thinking and authentic STEM practices. This study employed a Research and Development design using the ADDIE model, limited to Analysis, Design, and Development stages. Four experts in content, media, and instructional design, together with a professional science teacher, participated in validating the product, while 86 Grade VII junior high school students from two schools in East Kalimantan were involved in assessing its practicality. Data was collected through expert validation sheets and student response questionnaires using a four-point Likert scale, and scores were analyzed by converting them into percentages to determine validity and practicality categories. The expert validation results showed an average score of 93%, indicating a very good level of feasibility, with animated videos receiving the highest score of 96%. Student responses also demonstrated strong acceptance, with an average score of 83.96% categorized as very good, reflecting high levels of clarity, engagement, and relevance. These findings indicate that integrating SSI, STEM–EDP frameworks, and animated media strengthens students’ conceptual understanding and supports meaningful learning experiences. Overall, the developed learning materials are theoretically valid and practically feasible, offering a pedagogical innovation that bridges scientific content, environmental context, and engineering-based problem solving for junior high school science education.